Ordnungsbildung und Erkenntnisprozesse - Valk, Rüdiger (Hamburg University Press, 2006)
Formation of order and cognition are interdependent. Knowledge presupposes the observation of order structures or their creation through abstraction and modelling. Contributions from different areas of university research examine structures that relate to (partially) autonomous actors (or agents) and the dynamic processes in which they are developed. Processes of knowledge that take place in this context require structures of order that can be experienced interobjectively, and in some cases can also be grasped in symbolism and rituals, even if these structures are created simultaneously with processes of action or knowledge. Recursive references can lead to forms of self-organization. In more highly developed structures, aspects of knowledge, learning (and forgetting) can be included and additionally strengthened or weakened by emotional states.On November 5, 2005, scientists came together for a workshop on "Formation of Order and Knowledge Processes" at the University of Hamburg. In this volume, numerous of the given talks and articles are collected.